Assessing the working practices and the inclusive programs to students with disabilities in the Egyptian museums: challenges and possibilities for facilitating learning and promoting inclusion - Zakaria, Nevine Nizar (Frontiers in Education, 2023)
Following the implementation of 2018’s laws on the rights of Persons with Disabilities (PWDs) in Egypt, Students with Disabilities (SWDs) have both legal and moral rights to meaningful learning opportunities and inclusive education. Despite that, SWDs still have very limited education resources which limit their career aspirations and quality of life. In this respect, education whether as part of formal education or lifelong learning is central to the museum’s mission. Museums can be compared to universities and libraries for their contribution to non-formal education and lifelong learning. Further, phrases such as “inclusivity”, “accessibility”, and “diversity” were notably included in the newly announced museum definition by ICOM (2022) emphasizing museums’ obligations to embrace societal issues and shape a cultural attitude concerning disability rights, diversity, and equality together with overcoming exclusionary educational practices. In response to the ongoing national efforts toward supporting the rights of PWDs, Egyptian museums conducted several inclusion initiatives for PWDs including access programs for SWDs. Even though these initiatives take place on a small scale with short-term programs and individual efforts, they affirmed the potentiality of Egyptian museums in supporting learning beyond the formal education system. Thus, the study seeks to investigate the existing resources and inclusive practices in Egyptian museums to achieve non-formal education for SWDs. The study employed qualitative research approaches to answer a specific question: ‘to what extent the Egyptian museums can create a conducive learning environment for SWDS as well as contribute to curriculum topics and educational content that will support the public school system'. The study is not only aiming to assess the effectiveness of Egyptian museums in facilitating learning for SWDs but further examines the capability of Egyptian museums in contributing to informal and non-formal learning for SWDs and striving for inclusive education inspired by the social model that fosters inclusive educational programs and adopts a human rights-based approach to disability.